A scaffold‐free Bio 3D nerve conduit for repair of a 10‐mm peripheral nerve defect in the rats. Issue 2 (14th November 2019) - Takeuchi, Hisataka; Ikeguchi, Ryosuke; Aoyama, Tomoki; Oda, Hiroki; Yurie, Hirofumi; Mitsuzawa, Sadaki; Tanaka, Mai; Ohta, Souichi; Akieda, Shizuka; Miyazaki, Yudai; Nakayama, Koichi; Matsuda, Shuichi
Abstract: Introduction: A Bio 3D printed nerve conduit was reported to promote nerve regeneration in a 5 mm nerve gap model. The purpose of this study was to fabricate Bio 3D nerve conduits suitable for a 10 mm nerve gap and to evaluate their capacity for nerve regeneration in a rat sciatic nerve defect model. Materials and Methods: Eighteen F344 rats with immune deficiency (9–10 weeks old; weight, 200–250 g) were divided into three groups: a Bio 3D nerve conduit group (Bio 3D, n = 6), a nerve graft group (NG, n = 6), and a silicon tube group (ST, n = 6). A 12‐mm Bio 3D nerve conduit or silicon tube was transplanted into the 10‐mm defect of the right sciatic nerve. In the nerve graft group, reverse autografting was performed with an excised 10‐mm nerve segment. Assessments were performed at 8 weeks after the surgery. Results: In the region distal to the suture site, the number of myelinated axons in the Bio 3D group were significantly larger compared with the silicon group (2, 548 vs. 950, p < .05). The myelinated axon diameter (MAD) and the myelin thickness (MT) of the regenerated axons in the Bio 3D group were significantly larger compared with those of the ST group (MAD: 3.09 vs. 2.36 μm; p < .01; MT: 0.59 vs. 0.40 μm, p < .01). Conclusions: This study indicates that a Bio 3D nerve conduit can enhance peripheral nerve regeneration even in a 10 mm nerve defect model.